2019
DOI: 10.1158/1055-9965.epi-19-0089
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mortality-to-Incidence Ratio with Survival Analyses in Assessing Racial Breast Cancer Disparities Across South Carolina Counties

Abstract: The mortality-to-incidence rate ratio (MIR) provides a population-based measure of survival which accounts for incidence. The use of MIR as a surveillance tool has shown that South Carolina (SC) exhibits more extreme racial differences in cancer incidence, mortality and MIR than other states or the nation. We assessed the effectiveness of MIR as a proxy for 5-year survival time (5YST) among breast cancer (BrCa) patients in South Carolina. Methods: The 5YST was computed from data on BrCA cases which were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Mortalityto-incidence ratios (MIR) have been used for more than 40 years, first as a measure of completeness of cancer registries (13,14). Where quality of data is good, MIR can be a valid proxy indicator for survival estimates (calculated as 1-MIR) (14)(15)(16), and has already been used in multiple cancer types (17)(18)(19)(20)(21), including melanoma (22)(23)(24). Despite this, the use of MIR for survival estimation is mathematically questionable as the calculation does not use the same population for incidence and mortality (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortalityto-incidence ratios (MIR) have been used for more than 40 years, first as a measure of completeness of cancer registries (13,14). Where quality of data is good, MIR can be a valid proxy indicator for survival estimates (calculated as 1-MIR) (14)(15)(16), and has already been used in multiple cancer types (17)(18)(19)(20)(21), including melanoma (22)(23)(24). Despite this, the use of MIR for survival estimation is mathematically questionable as the calculation does not use the same population for incidence and mortality (13).…”
Section: Introductionmentioning
confidence: 99%
“…MIR is a good tool for international comparisons, as it is easily calculable with access to good quality data and using standardized rates which allows cross-country comparison (25). Studies on various types of cancer in OECD countries also discussed the potential of MIR as a measure for evaluation the success of cancer surveillance and screening (16,17,26). Studies generally found reverse correlation between healthrelated expenditure and MIR or development and MIR in multiple cancer types (18,20,23).…”
Section: Introductionmentioning
confidence: 99%